The Relationship of Coping Mechanisms with Anxiety Levels in Cancer Patients - Hidayat, Rahmat; rosmiati (Omni Health Journal, 2025)
Background : Cancer is one of the chronic diseases that not only affects physical conditions, but also causes severe psychological stress. One of them is anxiety, anxiety in cancer patients can arise from receiving a diagnosis, during treatment, to facing the uncertainty of the prognosis. Objective: The purpose of this study was to determine the relationship between the coping mechanism and the level of anxiety in cancer patients. Methods: This study was conducted quantitatively with a cross sectional approach using questionnaires to measure coping mechanisms and anxiety levels, this study involved 60 cancer patients undergoing treatment in hospitals. Results: The results of the analysis showed that most respondents (36.7%) used adaptive coping mechanisms but still experienced mild to severe anxiety. The Chi-Square test showed a weak association between coping mechanisms and anxiety levels (p = 0.004) suggesting that regardless of the relationship, adaptive coping has not been fully effective in lowering anxiety. Conclusion: Researchers recommend the development of educational programs and psychological assistance to address anxiety and can explore other factors that may affect cancer patients' anxiety.